The threatening but unpredictable Sarcoptes scabiei: first deadly outbreak in the Himalayan lynx, Lynx lynx isabellinus, from Pakistan - Hammed, Khalid; Alassad, Samer; Ud Din, Jaffar; Nawaz, Muhammad Ali; Rossi, Luca (Parasites & Vectors, 2016)
Although neglected, the mite Sarcoptes scabiei is an unpredictable emerging parasite, threatening human and animal health globally. In this paper we report the first fatal outbreak of sarcoptic mange in the endangered Himalayan lynx (Lynx lynx isabellinus) from Pakistan. A 10-year-old male Himalayan lynx was found in a miserable condition with severe crusted lesions in Chitral District, and immediately died. Post-mortem examination determined high S. scabiei density (1309 mites/cm2 skin). It is most probably a genuine emergence, resulting from a new incidence due to the host-taxon derived or prey-to-predator cross-infestation hypotheses, and less probable to be apparent emergence resulting from increased infection in the Himalayan lynx population. This is an alarming situation for the conservation of this already threatened population, which demands surveillance for early detection and eventually rescue and treatment of the affected Himalayan lynx Peer reviewed